The effect of tax digitalization and the level of tax understanding on individual taxpayer reporting compliance at the Cilegon Primary Tax Office - Erlina Sari Pohan; Yongky Rangga Yuda Nugraha; Alya Tiara Safitri (WIM Solusi Prima, 2026)
Tax compliance refers to the condition in which taxpayers fulfill and comply with their tax obligations and exercise their tax rights in accordance with the applicable tax regulations. Taxpayer reporting compliance is one of the most important keys to maximizing state revenue. Although the number of registered individual taxpayers has increased each year, compliance with the submission of Annual Tax Returns (SPT) by individual taxpayers continues to fluctuate. One of the contributing factors is the low level of understanding of tax systems, regulations, and procedures. Although the number of registered taxpayers has increased, not all taxpayers consistently fulfill their tax obligations. One contributing factor is changes in employment status or retirement, which may result in a taxpayer identification number (TIN) becoming inactive. In addition, some taxpayers still perceive that tax reporting obligations are entirely the responsibility of their employers. This misconception is primarily due to a lack of understanding of changes in the tax system. This study aims to examine the effect of tax digitalization and the level of tax understanding on individual taxpayer reporting compliance. The research employs a quantitative method using primary data collected through Likert-scale questionnaires. The sample consists of 100 individual taxpayers who submitted their Annual Tax Returns at the Cilegon Primary Tax Office (KPP Pratama Cilegon), selected using an incidental sampling technique. The results indicate that both partially and simultaneously, tax digitalization and the level of tax understanding have a significant effect on individual taxpayer reporting compliance.